2004
DOI: 10.1038/ncb1091
|View full text |Cite
|
Sign up to set email alerts
|

The tumour suppressor RASSF1A regulates mitosis by inhibiting the APC–Cdc20 complex

Abstract: The tumour suppressor gene RASSF1A is frequently silenced in lung cancer and other sporadic tumours as a result of hypermethylation of a CpG island in its promoter. However, the precise mechanism by which RASSF1A functions in cell cycle regulation and tumour suppression has remained unknown. Here we show that RASSF1A regulates the stability of mitotic cyclins and the timing of mitotic progression. RASSF1A localizes to microtubules during interphase and to centrosomes and the spindle during mitosis. The overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
323
4
8

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 289 publications
(348 citation statements)
references
References 29 publications
13
323
4
8
Order By: Relevance
“…The tumor suppressor RASSF1A is degraded at the G 1 -S transition Previous studies have suggested a growth-inhibitory function of RASSF1A at G 1 (Shivakumar et al, 2002;Rong et al, 2004) and during mitosis (Song et al, 2004;Vos et al, 2004). Thus, we reexamined the ability of RASSF1A to affect the cell cycle progression in various cell lines (U2OS, SaoS2, H1299, A549, MCF7, HeLa and 293T).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The tumor suppressor RASSF1A is degraded at the G 1 -S transition Previous studies have suggested a growth-inhibitory function of RASSF1A at G 1 (Shivakumar et al, 2002;Rong et al, 2004) and during mitosis (Song et al, 2004;Vos et al, 2004). Thus, we reexamined the ability of RASSF1A to affect the cell cycle progression in various cell lines (U2OS, SaoS2, H1299, A549, MCF7, HeLa and 293T).…”
Section: Resultsmentioning
confidence: 99%
“…RASSF1A regulates the mitotic progression, microtubule dynamics (Song et al, 2004;Vos et al, 2004) and G 1 -S transition (Fenton et al, 2004). The frequently observed downregulation of RASSF1A expression in human tumors has in many cases been attributed to promoter methylation (Agathanggelou et al, 2005), however, other potential causes have not been revealed yet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations